The Dilemma of Special vs. Inclusive Education in Tanzanian Public Primary Schools: Stakeholders' Perspectives - Sanga, Ben (Indonesian Journal of Disability Studies, 2025)
The effectiveness of special versus inclusive education settings in addressing the learning difficulties students with disabilities encounter in Tanzanian public primary schools has not received as much attention. Regardless of the Tanzania’s efforts to ensure a better education for students with special needs, a proper approach to executing such education has been yet debatable. Of all the conflicting ideas, nevertheless, less has been done to examine the current situation and challenges in the practice of special and inclusive education in Tanzanian public primary schools. This study examined the dilemma of special vs. inclusive education in Tanzanian public primary schools: stakeholders' perspectives. Specifically, the study examined the current practice, challenges, and stakeholders’ perspectives on special and inclusive education in Tanzanian public primary schools. The study employed a case study research design, whereby interviews and focus group discussions were used to collect data. The study found slight variations in the level of severity among the challenges facing both special and inclusive education which include inaccessibility and inadequacy of learning materials, classrooms, special teachers, and meal funds. The study recommended that the government as a main funder of education allocate sufficient budgets to finance both special and inclusive public primary schools to enable the provision of education in a friendly manner to students with disabilities.